The Quest for Solidarity in a Failed Prescriptive and Aspirational Cosmopolitanism: African Travel Narratives and Duality of Cross-Cultural Encounters - Munyangeyo, Theophile (My University, 2023)
The theme of travel has occupied a central position in African literature, as it serves as a conduit for exploring the complexities of cross-cultural interactions and the pursuit of solidarity. Travel narratives have highlighted aspirations for north-south solidarity, where the mirage of Western life represents self-fulfilment. Cross- community travel is also seen as a vital opportunity for cultural learning and social solidarity, embodying prescriptive and aspirational cosmopolitanism. However, within colonial and early post-colonial novels, authors also began portraying many challenges of physical and introspective journeys as reflections of failed solidarity. In this vein, travel narratives in African literature began to challenge the notion of solidarity as an idealistic aspiration and instead reflected the harsh realities faced by individuals in their quest for self-fulfilment and a sense of belonging. This paper explores and analyses the representation of solidarity in African literature, focusing on the duality of cross-cultural encounters and their implications for failed prescriptive and aspirational cosmopolitanism. Using Historical and Cultural Context method with references to Reader-Response Theory, this study sheds light on the complexities and consequences of failed solidarity encounters. The findings reveal that cosmopolitan ideals, whether prescriptive or aspirational, cannot bridge the gaps caused by social, economic, and political disparities without acknowledging and addressing power imbalances and structural inequalities between nations and communities. By critically examining the representations of different encounters of failed solidarity, this study contributes to offering insights into alternative pathways to genuine and transformative solidarity, ultimately contributing to a pragmatic understanding of borderless cosmopolitan ideals.
PUBLISHED
Keywords: African literature; Travel narratives; Solidarity; Narrative enquiry; Prescriptive and aspirational cosmopolitanism; Cross-cultural encounters; Identities in Transformation; Inclusive Society; International Development; International Integration; Cultural Identity; Exile literature; French Language/Literature; Language and/or Literature, Modern; Language and/or Literature, Poetry; Literary Criticism; Literary History; Literary theory; Literature and cultural history of the Enlightenment; Literature, philosophy and ideology; Migration Studies; Attitudes; Community; Communication; Culture; Education; Employment; Globalization; Literature; Youth